Extracellular Vesicles Derived from M2 Microglia and Enriched in miR‑27b‑3p Attenuate Mitochondria‑Dependent Endothelial Apoptosis via the MKK4/JNK Pathway and Alleviate BBB Disruption After Intracerebral Hemorrhage - Junjie Gong; Jing Li; Di Wu; Anqi He; Kexin Li; Zhijuan Chen; Mingyu Zhao; Mengyao He; Yuchi Zhang; Jing Feng; Yuheng Liu; Zengguang Wang (Molecular Neurobiology, 2026)
Intracerebral hemorrhage (ICH) is a life-threatening cerebrovascular disorder frequently accompanied by blood–brain barrier (BBB) disruption. Endothelial apoptosis is a key contributor to BBB damage, leading to loss of barrier function, exacerbation of brain edema and inflammation, and a cascade of adverse outcomes. Previous studies have shown that extracellular vesicles (EVs) released from M2-polarized microglia are enriched in neuroprotective miRNAs; however, their effects on endothelial cells after ICH and the underlying mechanisms remain unclear. This study aimed to determine the protective effects of M2‑EVs and their enriched miRNAs on vascular endothelial cells after ICH and to elucidate the relevant target genes and signaling pathways. Microglia were polarized to the M2 phenotype by IL‑4 stimulation, and EVs were isolated from M0‑ and M2‑polarized microglia. EVs were characterized by Western blotting, nanoparticle tracking analysis (NTA), and transmission electron microscopy (TEM). The effects of M2‑EVs on endothelial cells were evaluated in both in vitro and in vivo ICH models. In vitro , transendothelial electrical resistance, TUNEL staining, CCK‑8 assays, Western blotting, immunofluorescence, and TEM were used to assess endothelial apoptosis and tight junction integrity. In vivo , BBB disruption and brain edema after ICH were assessed by EB extravasation, MRI, and brain water content, and endothelial apoptosis and tight junction damage were further examined by Western blotting, immunofluorescence, and TEM. Neurological recovery was evaluated using neurological severity scores, rotarod and corner tests, and gait analysis. Candidate miRNAs were screened by sequencing, and their therapeutic effects, target genes, and downstream signaling pathways were validated. In both in vitro and in vivo ICH models, M2‑EVs reduced endothelial apoptosis, preserved tight junctions, and attenuated BBB disruption, thereby alleviating brain edema, limiting hematoma expansion and ameliorating neurological deficits in mice. miRNA sequencing identified miR‑27b‑3p, enriched in M2‑EVs, as a key mediator. miR‑27b‑3p directly targeted MKK4 and reduced phosphorylation of MKK4 and JNK in endothelial cells. This, in turn, increased the Bcl‑2/Bax ratio, helped maintain mitochondrial homeostasis, decreased mitochondrial release of cytochrome c (Cyt c), and lowered the expression of the downstream apoptotic effector Caspase‑3. As a result, endothelial apoptosis was suppressed and tight junction integrity was maintained, which mitigated BBB‑related neurological dysfunction after ICH. This study demonstrates that M2‑EVs, particularly those enriched in miR‑27b‑3p, protect the BBB after ICH by targeting the MKK4/JNK signaling pathway, increasing the Bcl‑2/Bax ratio and stabilizing mitochondrial function. These changes reduce Cyt c release and Caspase‑3 expression, thereby inhibiting endothelial apoptosis, preserving BBB integrity and improving neurological outcomes in mice at 3 days post‑ICH. Together, these findings suggest that miR‑27b‑3p carried by M2‑EVs represents a promising neurovascular protective strategy with considerable translational potential for the treatment of hemorrhagic stroke. Graphical Abstract